Building resilient relationships with suppliers in the B2B market = Budowanie odpornych na zakłócenia relacji z dostawcami na rynku B2B - Wieteska, Grażyna (Zielona Góra: Faculty of Economics and Management Press)
The growing uncertainty of business environment that negatively influences the contemporary supply chains is one of the major challenges for today's managers. The literature recommends the development of resistant supply chains, defining them as adaptive and flexible. However, there are a few scientific publications that directly link to the area of Supplier Relationship Management in this regard.
Keywords: odporność; zakłócenie; łańcuch dostaw; elastyczność; adaptacyjność; resistance; disruption; supply chain; flexibility; adaptability